2019
DOI: 10.11118/actaun201967030811
|View full text |Cite
|
Sign up to set email alerts
|

Are Partnerships Enhancing Tourism Destination Competitiveness?

Abstract: The competitiveness and networking in tourism destinations is a well discussed topic among tourism scholars. However, the influence of partnerships of destination stakeholders on tourism competitiveness is under‑researched. This paper contributes to the recent debate on partnerships and tourism destination competitiveness, including the gargantuan compilations of competitiveness factors by Ritchie and Crouch (2003), or Dwyer and Kim (2003), by examining the link among these two variables. The central question … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 28 publications
1
3
0
Order By: Relevance
“…Second, the result of this study that increased supply chain integration leads to higher corporate performance confirms the current knowledge that when a supply chain is integrated, performance of the firm can be enhanced [81]. Moreover, the positive influence of supply chain integration on MICE destination competitiveness identified in this research corroborates the argument of previous studies that increased partnerships among stakeholders could trigger an enhancement of destination competitiveness [90].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Second, the result of this study that increased supply chain integration leads to higher corporate performance confirms the current knowledge that when a supply chain is integrated, performance of the firm can be enhanced [81]. Moreover, the positive influence of supply chain integration on MICE destination competitiveness identified in this research corroborates the argument of previous studies that increased partnerships among stakeholders could trigger an enhancement of destination competitiveness [90].…”
Section: Discussionsupporting
confidence: 88%
“…For infrastructure to be well developed, to offer satisfactory activities, and to provide high-quality services to visitors, collaborative work among stakeholders is essential. In fact, Kvasnová, Gajdošík, and Maráková [90] identified that the degree of partnership among tourism stakeholders has a positive influence on destination competitiveness. Moreover, enhanced supply chain integration has been known to improve product quality and the level of customer service [91].…”
Section: Supply Chain Integration and Mice Destination Competitivenessmentioning
confidence: 99%
“…Interest groups that should cooperate in the destination are often identified differently (Sheehan & Ritchie, 2005 ; Friedman & Miles, 2006 ; Bieger, 2008 ; UNWTO, 2019 ; Kvasnová et al, 2019 ). Beritelli et al ( 2015 ) draw attention to the difficulty of reaching a consensus with the simultaneous involvement of all stakeholders with conflicting interests in the strategic process.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In the literature, most of the relevant research has been conducted on destinations that are widely preferred such as mass tourist locations but which are less competitive than alternative tourism examples (Benedetti, 2000;Dragi cevi c et al, 2009;Hallman et al, 2014;Zhou et al, 2015;Reisinger et al, 2018;Gupta and Singh, 2019;Dodds and Holmes, 2020;Mili cevi c et al, 2020;Marasigan and Borbon, 2021). In addition, it has been observed that only tourists (Chen et al, 2011(Chen et al, , 2016Hallman et al, 2014;Wong, 2018;Mili cevi c et al, 2020;Bire et al, 2021) or stakeholders (Enright and Newton, 2004;Lee and King, 2008;Armenski et al, 2012Armenski et al, , 2017Goffi and Cucculelli, 2012;Kvasnov a et al, 2019;Marasigan and Borbon, 2021) are preferred as the population in the majority of studies conducted on destination competitiveness. This reveals that there is a need for a comparative and holistic study on the competitiveness of tourism destinations with limited and unique tourism products in the form of alternative tourism.…”
Section: Introductionmentioning
confidence: 99%